Novel Wire Gripper for Robotics Picking of Small Green Parts From Powder Bed of Binder Jet Metal Additive Manufacturing - Abdulhamid Mathkur; Yanen Huang; Kenji Shimada (IEEE Access, 2025)
The production revolution has materialized through Binder jet metal 3D printing because this technology creates detailed customized parts efficiently. The process achieves better results when parts are operated near each other because it reduces disturbance to the powder material. The protection of workers in addition to their safety is funda- mental. The essential elements for enhanced performance in- clude non-harmful material selection and controlled dust reg- ulation combined with ergonomic product optimization. The entire workforce needs complete training on safe protocols for operation. We can achieve improved quality and efficiency for binder jetting through proper factor resolution which will result in successful manufacturing of complex high-value components. Basic mechanical grippers do not have enough ability to handle polished parts, as their solid force can damage the components. Our research results in a special gripper system that is suitable for robotics used for safe depowdering operations. The adaptable gripper system fits different part geometries to decrease the chance of component deformation or fracturing. A combination of 304 stainless steel wires integrated with a PLA body allows the device to achieve precise handling and control together with versatile operation. The new gripper system extends its reach into tight vertical placement spaces, achieving improved comprehensive depowdering capabilities. Our work focuses on cutting down postprocessing times as we strive to reach higher levels of productivity. The development enhances the essential nature of advanced tooling systems for the advancement of binder jetting technology and process optimization within additive manufacturing. The development of these solutions makes binder jet metal 3D printing the advanced technology for fabricating intricate high-performance components that serve multiple industrial uses. The study improves the advancement of additive manufacturing by creating new possibilities for scalable and adaptable production systems in the modern industry.